2010
DOI: 10.1002/lary.20985
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal sensory deficits in patients with chronic cough and paradoxical vocal fold movement disorder

Abstract: Aberrant laryngeal sensation was identified in patients with PVFM and chronic cough. This response, however, normalized following a limited course of respiratory retraining, corresponding with improved patient symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 16 publications
2
54
0
3
Order By: Relevance
“…The retrospective review looked at 16 patients with CRC who underwent a series of breathing retraining exercises with a speech pathologist including rhythmic breathing, breathing with vocal resistance, pulsed exhalation, and abdominal focus at rest. 78 Fifteen patients reported improved cough symptoms. The reflux symptom index score improved by a mean of 3.74 points and all patients improved (P<0.01).…”
Section: Pharmacologic Therapy Neuromodulatorsmentioning
confidence: 98%
See 2 more Smart Citations
“…The retrospective review looked at 16 patients with CRC who underwent a series of breathing retraining exercises with a speech pathologist including rhythmic breathing, breathing with vocal resistance, pulsed exhalation, and abdominal focus at rest. 78 Fifteen patients reported improved cough symptoms. The reflux symptom index score improved by a mean of 3.74 points and all patients improved (P<0.01).…”
Section: Pharmacologic Therapy Neuromodulatorsmentioning
confidence: 98%
“…74 The review included one single blinded randomized controlled trial, 29 three prospective noncomparison studies, [75][76][77] and one retrospective review. 78 Meta-analysis was not possible so the included studies are discussed separately below.…”
Section: Non-pharmacologic Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have reported on the co-occurrence of dysphonia and PVFM. Murry et al [36] reported a significant reduction in dysphonia symptoms after treatment in patients with PVFM and chronic cough and Vertigan et al [41] reported similar findings. In our study, those who reported feelings of control and activity improvement also reported a greater reduction in the severity of their voice complaints.…”
Section: Discussionmentioning
confidence: 85%
“…There is recent evidence, however, that even minimal stimulation caused by routine vocal fold vibration is sufficient to instigate cough in those with hypersensitivity syndrome. 17,18 Complicating this association is that GERD is similarly implicated. 19 It is important to study the differential effects of these two potential triggers to advance the understanding of idiopathic chronic cough pathophysiology and to identify potential methods and targets for prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%